1. The problem statement, all variables and given/known data "Let f(x)=x. Define the change of variable y=5x. Then this implies g(y)=y/5. [we have g(y)=f(x(y))=f(y/5) and f(x)=g(y(x))=g(5x)] " 2. Relevant equations N/A 3. The attempt at a solution I don't understand the above statement. If we define y=5x, then WHY does it imply g(y)=y/5? Shouldn't it be f(y)=y/5? WHY do we need to introduce a new function g? (here we are doing a change of variable on the independent variable x, how come the dependent variable also changes?) Also, WHY do we have g(y)=f(x(y)) and f(x)=g(y(x))? I don't understand this. I think my concepts in this topic of change of variables is screwed up. Can someone please explain? Thank you!